Programowanie rozwoju ekonomii społecznej w perspektywie socjologicznej. Zarys problematyki = Programming the development of the social economy in sociological perspective. An outline of the issues - Górnicka, Krystyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main purpose of this article is to present programming the development of social economy as a potential subject of sociological analysis. This problem has so far been rarely discussed by the researchers. Today, there is a growing need to combine measures taking into account the economic balance of the social activities directed to help a man threatened with marginalization. At the same time the financial resources allocated for activities related to social economy are being gradually increased.
Keywords: ekonomia społeczna; socjologia; programowanie; social economy; programming; sociology